A Computer Adaptive Measure of Delay Discounting. (December 2018) - Mahalingam, Vaishali; Palkovics, Michael; Kosinski, Michal; Cek, Iva; Stillwell, David
Delay discounting has been linked to important behavioral, health, and social outcomes, including academic achievement, social functioning and substance use, but thoroughly measuring delay discounting is tedious and time consuming. We develop and consistently validate an efficient and psychometrically sound computer adaptive measure of discounting. First, we develop a binary search–type algorithm to measure discounting using a large international data set of 4, 190 participants. Using six independent samples ( N = 1, 550), we then present evidence of concurrent validity with two standard measures of discounting and a measure of discounting real rewards, convergent validity with addictive behavior, impulsivity, personality, survival probability; and divergent validity with time perspective, life satisfaction, age and gender. The new measure is considerably shorter than standard questionnaires, includes a range of time delays, can be applied to multiple reward magnitudes, shows excellent concurrent, convergent, divergent, and discriminant validity—by showing more sensitivity to effects of smoking behavior on discounting.